(3TQM GdCfehPLs - (3eLghds
(3ChdgG (B:s
(3GdcdeI (B( (3daX (B) (3eaQO bHd GdTQhY ai GdebUhO dGHO ef JbOje ebOeI gPg Ef WGdH cd TF jfHZi Cf jJUhQ ChdkG Pdc GdTF HhLg ef GdhLhg s
(3BNQgG (B:s
(3YUefG Gddg ef TQhQge hQO Edjge HdWag cjOge ai fMhQge GdMeO ddg Ydi GdJeGe h(B( (3Ydi (B) (3GdQShd CaVd GdSdGe s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs